Extraction et Isolement des curcuminoïdes à partir des rhizomes de curcuma longa L. - Lazreg khadidja; Touat ferdaous; Mahdjoubi Hadj Aissa (Université Amar Thelidji – Laghouat Faculté de Technologies Département de Génie Des Procédés, 2022)
The objective of the work presented in this thesis is the extraction of curcumin from turmeric then the isolation of the latter by solid liquid extraction and by crystallization in order to improve the concentration of curcumin. The results show an improvement in purity for each step, for the isolation of crude from oleoresin there is an increase from 27.2% to 45.6% and similarly the crystallization step leads to an increase of 53.5%, these values agree with the results obtained for the measurement of the melting points. The antioxidant activity study of the products isolated by the DPPH• test shows that the activity of crystallized curcumin is comparable to the activity of ascorbic acid used as a standard .
Option : Génie Pharmaceutique